Analysis of Traffic Congestion and Remedial Measures at Batu Pahat, Johor - Sazlan, Nur Afifah; Nasradeen Ali Khalifa Milad, (Recent Trends in Civil Engineering and Built Environment, 2024)
Abstract: Traffic congestion is a worldwide problem that wastes time and energy while also polluting the environment. The growing number of vehicles on the road, combined with increasing urbanization, creates a problem of congestion, which further complicates and hazard on city roads. Traffic congestion in town has gotten worse in recent years as a result of increased traffic volume and development, especially in Batu Pahat, Johor. The aims of this research are to identify the factors that cause the congestion at selected area. To investigate the traffic congestion toward the factors caused the congestion, and to determine the remedial measures to reduce this traffic congestion. For this study, mixed methods will be use, including document review, observation, and a questionnaire. This study describes the factors that contribute to traffic congestion on urban roads as well as potential solutions to the problem of traffic congestion. Furthermore, it would be beneficial in reducing the number of private motorized vehicles in the area in order to reduce traffic congestion and to prepare Batu Pahat town as a low-carbon city in the future.